PERFORMANCE EVALUATION OF TWO BEAN HARVESTERS - Nagaoka, Alberto Kazushi; Martyn, Peter John; Fernandes, Haroldo Carlos; Zito, Roberto Kazuhiko; Cecon, Paulo Roberto (Revista de Ciências Agroveterinárias, 2005)
The objective of this research was to evaluate the performance of two bean harvesters; the first is identified by having indented disk, and the second by having court of lamina. The project was realized in São João Farm (MG), Coimbra Country. The performance of the two equipment were compared evaluating: no extracted plants, damage loss, fuel consumption and theoretical field capacity. The beans used for this research was Ouro Negro type III. The tractor used to pull the harvesters was the VALMET 68 Cafeeiro, with 43 kW engine power, 1,120 mm of track, 0.78 m.s-1 and two speeds of 1.25 m.s-1. The data was analyzed using split plot design the harvesters in the parcels and the speeds of tractor in the sub parcels, with six repetitions. The statistical analysis showed that the number of no extracted plants were greater (P < 0.05) for indented disk harvester with 0.78 ms-1 speed. The damage loss was significantly higher (P< 0.05) the equipment with court lamina was used. The specific fuel consumption was greater (P<0,05) in 0,78 m.s-1 speed than 1.25 m.s-1 within harvesters but not between harvesters. The greater theoretical field capacity was 0,54 ha.h-1.